2004
DOI: 10.1021/je049789+
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal VLE Measurements for Difluoromethane + Dimethyl Ether and an Evaluation of Hydrogen Bonding

Abstract: Vapor−liquid equilibria (VLE) data for the difluoromethane (R32) + dimethyl ether (RE170) system were measured with the aim of completing our study of hydrogen bonding between hydrofluorocarbons (HFCs) and dimethyl ether. The measurements were taken in an apparatus based on a static analytical method at temperatures ranging between (258.15 and 293.15) K. The R32 + RE170 system shows a slight negative deviation from Raoult's law that is attributed to hydrogen bonding between RE170 and R32. This H bonding was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Comparison of published vapor pressures [dev = p σ – p σ,cal ] with values calculated with eq (this work), derived from experimental U (2) increments: purple ▲, Wu and Yin; red ■, Corvaro et al; blue ◀, Ihmels and Lemmon; green ▶, Valtz et al; purple ★, Kennedy et al; green ◆, Fedele et al; green ∗, Bobbo et al; + , Daiguji and Hihara; maroon , Wu and Yin; aqua ---, Ihmels and Lemmon …”
Section: Resultsmentioning
confidence: 99%
“…Comparison of published vapor pressures [dev = p σ – p σ,cal ] with values calculated with eq (this work), derived from experimental U (2) increments: purple ▲, Wu and Yin; red ■, Corvaro et al; blue ◀, Ihmels and Lemmon; green ▶, Valtz et al; purple ★, Kennedy et al; green ◆, Fedele et al; green ∗, Bobbo et al; + , Daiguji and Hihara; maroon , Wu and Yin; aqua ---, Ihmels and Lemmon …”
Section: Resultsmentioning
confidence: 99%
“…In the fitting procedure, the critical pressure was fixed to be P c =5370.2 kPa [9]. The analysis of the recent literature showed that a total of 11 data sources are available [10][11][12][13][14][15][16][17][18][19][20]. The experimental results were also compared with the published data in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The reliability test is needed for the experimental data because of the errors caused by many reasons. , According to the chemical thermodynamics, the variables of T , P , x , y of any system are restricted by the phase rule and the activity coefficient can be linked to them. Therefore, the reliability of experimental data can be checked by the general formula of thermodynamics and the basic formula is activity coefficient form of the Gibbs–Duhem equation .…”
Section: Experimental Data and Discussionmentioning
confidence: 99%